Actually, what does teacher inherit? Epistem, doxa, or hoax: A case study on the topic of sets in Indonesia - Hendriyanto, Agus; Fitriana, Laila; Usodo, Budi; Wahyuni, Astri; Azizah, Nurul (Indonesian Journal of Science and Mathematics Education, 2025)
This research aims to evaluate a selected element of mathematical knowledge intended for teaching in Indonesian schools, namely the concept of sets. The evaluation assesses whether the information conveyed the criteria of knowledge that is Justified, True, and Believed (JTB). This research follows a qualitative approach with a case study design. The research involves 250 students and nine teachers from two different schools. The collected data was analyzed using the Constant Comparative Method (CCM) as the data analysis model. The study's findings reveal that beliefs with truth value only relate to interpreting sets as a well-defined collection of objects. However, teachers and students cannot prove their beliefs and cannot interpret well-defined as an individual's ability to determine a property P. Thus, the belief about sets as a well-defined collection of objects is merely doxa or true belief. This study emphasizes the importance of mathematics education in fostering justified true belief through a focus on critical thinking and conceptual justification, thereby minimizing the occurrence of the Zone of Concept Image Difference (ZCID) between teachers and students.